ANALISIS PENGARUH LINGKUNGAN KERJA, KOMPENSASI, STRES KERJA TERHADAP SEMANGAT KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN - Rismayanti Rasdam; Syamsu Alam; Andi Reni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
In the face of globalization era human resources play a very dominant role in the activities or activities or activities of the company. Success or failure of a company depends on the ability of human resources in carrying out the work given. This study aims to analyze the influence of Work Environment, Compensation, Job Stress on performance partially as well as the influence of Work environment, Compensation, Job Stress mediated by morale. This type of research is a causal associative using a quantitative approach. The population in this study is all of Inco Sorowako Hospital employees totaling 157 people. The sampling technique is a saturated sample. Techniques of collecting research data in the form of questionnaires and observations, as well as various data related to the research. The method of analysis used in this research is path analysis. The results showed that work environment, compensation, and work stress significantly influence work morale. The spirit of work has a significant effect on employee performance. While the work environment, compensation, and job stress significantly affect employee performance by mediating morale.